Water column baseline assessment for offshore Carbon Dioxide Capture and Storage (CCS) sites: Analysis of field data from the Goldeneye storage complex area. (July 2021) - Esposito, Mario; Martínez-Cabanas, María; Connelly, Douglas P.; Jasinski, Dominik; Linke, Peter; Schmidt, Mark; Achterberg, Eric P.
Highlights: Environmental monitoring for offshore carbon dioxide storage sites. Analysis of water column in situ measurements for the determination of baseline conditions at an experimental site for CO2 storage in the North Sea. Assessment of the variability between carbonate variables and physicochemical parameters at the near seabed for the identification of potential non-natural CO2 emissions at offshore storage sites. Abstract: Monitoring operations at the seafloor above a storage complex area are required to demonstrate that offshore storage of CO2 in the deep subsurface is safe and effective. Within the framework of the STEMM-CCS project, the Goldeneye area was identified as an offshore experimental site for CO2 storage. In this work, the physico-chemical characteristics of the water column at the Goldeneye site were determined by an in-depth analysis of measurements collated from CTD casts, discrete water samples and seafloor landers. The results showed a clear tidal, seasonal and inter-annual variability in the measured parameters within the monitoring period (Oct 2017- May 2019). Variations in pH and pCO2 over a single tidal cycle were in the order of ±0.008 and ±1.5 μatm, respectively. The temporal variability of water column carbonate chemistry parameters was further defined with the aim to provide a solid background for the discrimination from natural changes of potential impacts of CO2 emissions at the potential storage site. Here, we demonstrated how the combination of new and existing methods and technologies could be used for an effective assessment of water column conditions at a potential offshore carbon storage site.